Model-Observations Synergy in the Coastal Ocean - De Mey-Frémaux, Pierre; Ayoub, Nadia; Barth, Alexander; Brewin, Robert; Charria, Guillaume; Campuzano, Francisco; Ciavatta, Stefano; Cirano, Mauro; Edwards, Christopher A.; Federico, Ivan; Gao, Shan; Garcia Hermosa, Isabel; et al. (Frontiers in Marine Science, 2019)
Integration of observations of the coastal ocean continuum from regional oceans to shelf seas and estuaries/deltas with models can substantially increase the value of observations and enable a wealth of applications. In particular, models can play a critical role at connecting sparse observations, synthesizing them, and assisting the design of observational networks; in turn, whenever available, observations can guide coastal model development. Coastal observations should sample the two-way interactions between nearshore, estuarine and shelf processes and open ocean processes, while accounting for the different pace of circulation drivers, such as the fast atmospheric, hydrological and tidal processes and the slower general ocean circulation and climate scales. Because of these challenges, high-resolution models can serve as connectors and integrators of coastal continuum observations. Data assimilation approaches can provide quantitative, validated estimates of Essential Ocean Variables in the coastal continuum, adding scientific and socioeconomic value to observations through applications (e.g. sea-level rise monitoring, coastal management under a sustainable ecosystem approach, aquaculture, dredging, transport and fate of pollutants, maritime safety, hazards under natural variability or climate change). We strongly recommend an internationally coordinated approach in support of proper integration of global and coastal continuum scales, as well as for critical tasks such as community-agreed bathymetry and coastline products.